Phenology and Breeding Mechanisms of Calamus lobbianus Becc. and Calamus pygmaeus Becc. - Ng Win Seng,; Wong Sin Yeng,; Hashimah Elias,; Meekiong Kalu, (Tropical Life Sciences Research, 2024)
The floral biology of Calamus is relatively unknown except for several species. In this study, Calamus lobbianus and Calamus pygmaeus were selected to represent the non-climbing rattan of the Sundaland’s flagellate group. Observations on phenology, floral rewards and floral visitors as well as experiments on the breeding mechanism and operational sex ratio were performed for both species. For both species, anthesis started in the early morning for pistillate and staminate plants, ended by late noon (staminate plants) but lasted till the next day in pistillate plants for both species. Although both species appeared to be aseasonal in flowering, C. lobbianus exhibited a male-biased population while C. pygmaeus did not exhibit any sex bias. Nectar was observed to be extruded from the base of the petals of C. lobbianus of the staminate flowers and sterile staminate flowers of the pistillate plants. The concentration and volume of the nectar of the staminate flower and sterile staminate flower of C. lobbianus peaked at c. 11% and 9 ?L around 1100 (Day 1) and c. 13% and 8 ?L around 0930 (Day 1), respectively, but only appeared as a layer of glistening exudate in C. pygmaeus. Floral scent was not detected in any of the inflorescences of both species. Several insect visitors were observed to be the primary visitors of both Calamus species which include two species of Tetragonula, a species of Liostenogaster sp., and Stenodyneriellus sp. Experiments on breeding mechanism of C. lobbianus and C. pygmaeus indicate that both species are most likely apomictic. C. pygmaeus is capable of vegetative propagation through the rooting at the tip of inflorescence.